The interactive effect of affectionate nicknames and streamer type on streamer attitude in E-commerce live streaming: the mediating role of psychological closeness - Liu, Yuan; Liu, Maohong (Frontiers in Psychology, 2024)
BackgroundWith the widespread application of Artificial Intelligence technology in the field of E-commerce, human–machine relationships have attracted considerable attention within the field of psychology. Address forms, as crucial linguistic cues, have shown notable progress in advancing research on interpersonal relationships; however, a comprehensive understanding of the dynamics in interpersonal (or human–machine) relationships among interactors remains elusive. Therefore, based on Social Identity Theory, this paper explores the interactive effects and underlying mechanisms of affectionate nicknames and streamer type on streamer attitude in E-commerce live streaming, with consumers’ perceptions of psychological closeness serving as the mediating mechanism.MethodsTwo between-subjects experimental designs, both involving a 2 (Affectionate Nicknames: use vs. non-use) × 2 (Streamer Type: human streamer vs. virtual streamer) factorial structure, were conducted to test the hypotheses. Study 1, utilizing image materials, collected 368 samples on the Credamo to examine the interactive influence of streamer type and affectionate nicknames on streamer attitude. Study 2, employing video materials, gathered 370 samples on the same platform. While replicating and validating the findings of Study 1, it also revealed that the interactive effect of streamer type and affectionate nicknames on consumer’s streamer attitude is mediated by psychological closeness.ResultsThis paper finds that consumers’ psychological closeness differs significantly across different streamer types, leading to potential variations in consumer attitude toward streamer type within different linguistic communication contexts. Specifically, when consumers encounter human streamers, using affectionate nicknames elicits a more positive streamer attitude compared to not using them; conversely, when consumers encounter virtual streamers, not using affectionate nicknames results in a more negative streamer attitude compared to using them.ConclusionThis paper not only compares the linguistic and communicative distinctions between interpersonal relationships and human–machine relationships from a psychological perspective but also undertakes valuable empirical investigations into their interaction differences. Furthermore, it contributes to advancing research into consumer responses to commercial avatars and offers practical managerial guidance for businesses employing avatars in E-commerce live streaming practices.